The effects of music-induced emotions on English-Chinese bilinguals' resolution of standing ambiguity. - Ho, Sher Min. (2012)
Cross-linguistic studies have shown that speakers of different languages have differing strategies in resolving sentences with standing ambiguity (Felser, 2003; Shen, 2006) with most languages preferring NP2 or NP-low attachment (e.g. English, Danish) while some others prefer NP1 or NP-high attachment (e.g. Greek, German). The strategy taken by Chinese speakers remain controversial with some studies showing it to be a NP-low preferring strategy (Shen, 2006) while some others show otherwise (Cai, 2010). The strategies adopted by bilingual speakers have yet to be thoroughly explored. External factors like lexical factors (Felser, 2003) and animacy (Desmet et. al, 2006) are also found to be of influence on speakers’ strategies in resolving these sentences.